2006
DOI: 10.1097/01.jnen.0000240465.33628.87
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Analysis of Pilocytic Astrocytomas at 0.97 Mb Resolution Shows an Increasing Tendency Toward Chromosomal Copy Number Change With Age

Abstract: Brain tumors are the most common solid tumors of childhood, accounting for over 20% of cancers in children under 15 years of age. Pilocytic astrocytomas (PAs), World Health Organization grade I, are one of the most frequently occurring childhood brain tumors, yet little is known about genetic changes characterizing this entity. We have used microarray comparative genomic hybridization at 0.97 Mb resolution to study a series of PAs (n = 44). No copy number abnormality was seen in 64% of cases at this resolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
66
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 58 publications
10
66
2
Order By: Relevance
“…The second cytogenetic pattern is characteristic of secondary glioblastomas, which develop through progression from low-grade diffuse astrocytomas or anaplastic astrocytomas where TP53 mutation is the most frequent and earliest detectable genetic alteration [24,30]. Our results support and extend on this hypothesis by showing that, at the intratumoral cell level, early tetraploidization together with combined 1p36/19q13 losses are associated with low-grade astrocytomas and oligodendroglial tumors, respectively; of note, tetraploidy was similarly found in pilocytic grade I as well as grade II, diffuse astrocytomas as also reported by others [56,57]. In contrast, the ancestral tumor cell clones of high-grade gliomas are more likely associated with early occurrence of combined gains/amplification of the EGFR gene in chromosome 7, hemizygous or homozygous del (9p21) and/or deletion of the PTEN gene in chromosome 10q, followed by acquisition of complex karyotypes prior to tetraploidization.…”
Section: Discussionsupporting
confidence: 80%
“…The second cytogenetic pattern is characteristic of secondary glioblastomas, which develop through progression from low-grade diffuse astrocytomas or anaplastic astrocytomas where TP53 mutation is the most frequent and earliest detectable genetic alteration [24,30]. Our results support and extend on this hypothesis by showing that, at the intratumoral cell level, early tetraploidization together with combined 1p36/19q13 losses are associated with low-grade astrocytomas and oligodendroglial tumors, respectively; of note, tetraploidy was similarly found in pilocytic grade I as well as grade II, diffuse astrocytomas as also reported by others [56,57]. In contrast, the ancestral tumor cell clones of high-grade gliomas are more likely associated with early occurrence of combined gains/amplification of the EGFR gene in chromosome 7, hemizygous or homozygous del (9p21) and/or deletion of the PTEN gene in chromosome 10q, followed by acquisition of complex karyotypes prior to tetraploidization.…”
Section: Discussionsupporting
confidence: 80%
“…37 A recent report on genomic alterations of pilocytic astrocytoma using high-resolution array CGH revealed nonrandom multiple whole chromosomal gains in 14 (32%) of 44 pilocytic astrocytomas involving chromosomes 5, 7, 6, 11, 15, and 20. 15 Although this study, which employed array-CGH analysis, did not set out to discover the characteristic genetic changes of pilocytic astrocytoma, we compared the previous cytogenetic and molecular genetic results with the results of our study. In the result, we found that chromosome 8q24.3 was gained in the gene copy number in four of six pilocytic astrocytoma patients and one of four pilomyxoid astrocytoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Array CGH has also been applied to the neoplasm of the nervous system to find common genetic tumor aberrations to determine novel tumor suppressor genes that had been deleted and oncogenes that had been amplified, or to identify the tumor-specific and clinically relevant molecular genetic signatures. [15][16][17][18][19] In this study, we investigated the clinicopathological features of 11 circumscribed astrocytomas with focal (n ÂŒ 5) or diffuse (n ÂŒ 6) pilomyxoid features and compared them with 17 pilocytic astrocytomas from the hypothalamic/chiasmatic region in young children. In addition, to further delineate the genetic characteristics of pilomyxoid astrocytoma and the possible association with pilocytic astrocytoma, we compared the comprehensive genome copy number changes in pilomyxoid astrocytoma with those in pilocytic astrocytoma by high-resolution array CGH.…”
mentioning
confidence: 99%
“…Similarly, although chromosomal aberrations or amplification/deletion of specific genes related to cell cycle control, growth factor receptors and signal transduction pathways are commonly identified in other glioma subtypes (Koschny et al, 2002;Schmidt et al, 2002;Ohgaki et al, 2004;Ohgaki, 2005), most cytogenetic studies have shown that the majority of PAs have normal karyotypes. Structural aberrations involving chromosomes 6, 7, 8, 11, 17 and 19 have been reported in a few cases (Jenkins et al, 1989;Thiel et al, 1992;Agamanolis and Malone, 1995), and the most consistently identified cytogenetic changes involve gains on chromosomes 7 and 8 (White et al, 1995;Zattara-Cannoni et al, 1998;Sanoudou et al, 2000;Jones et al, 2006). We have previously identified a transcript on chromosome 8 whose expression is increased in PA (Sharma et al, 2006); however, no specific genes have been implicated on chromosome 7.…”
mentioning
confidence: 99%
“…All real-time PCR assays were performed in triplicate on an ABI PRISM 7900HT Sequence Detector System (ABI) as follows: 50 1C for 2 min, 95 1C for 10 min and 40 cycles of both 15 s at 95 1C and 60 sec at 60 1C. The reference gene, DOCK10, which was chosen to normalize the DNA input between individual DNA samples, is on chromosome 2 where no significant gains/losses were observed with both NimbleGen and Affymetrix array data in our 10 PA cases and in another study (Jones et al, 2006). (b) The upper panel demonstrates representative PAs with different percentages of cells within the tumor demonstrating HIPK2 nuclear staining; (i) >75%; (ii) 50-75%; (iii) 25-50%; (iv) o25% (scale, 100 mm).…”
mentioning
confidence: 99%